Efeitos ecotoxicológicos de pesticidas em Daphnia similis (Crustacea, Cladocera) : ensaios laboratoriais para a avaliação de um cenário real. - Kühl, Adelina Maria (2014)
Pesticides can enter the aquatic ecosystems in several ways, with leaching and runoff of agricultural areas as a major form. This phenomenon can be favored by different soil characteristics, but also by the properties of substances and practices applied by farmers. Thus, this study aimed to evaluate the sensitivity of Daphnia similis Straus 1820 (Crustacea, Cladocera) to three commercial pesticides (Siptran 500SC®, Dimilin® and Aproach Prima®), and also the potential risks of using these products in areas located nearby aquatic ecosystems through simulations of different scenarios in the laboratory. Therefore, acute toxicity tests were conducted with the individual formulations and with the eluate and leachate from soil artificially contaminated with concentrations of field and mixtures used in rural area of Maringá County, Paraná State. The results indicate a greater sensitivity of D. similis in relation to insecticide Dimilin® (toxic up to 5 ppb), followed by fungicide Aproach Prima® (EC50;48h: 47,33 ?g/L) and the herbicide Siptran 500 SC® (EC50;48h: 534,69 mg/L). It was also found that the applied and recommended and field dosages are higher for two the tested products than acute toxicity obtained for the cladocerans during the study. For the simulations performed with the data field all treatments were toxic for organism-test, especially fungicide Aproach Prima® and mixtures, which killed 100% of the individuals in 24 hours throughout the experiment. Thus, the results demonstrate the importance of tests with species that are not targets of the application of these products, as well as information about applied areas in the planning of laboratorial experiments to risk assessments and protection of aquatic organisms.